Coagulation fibrinolysis in sickle-cell disease - Gordon, P. A. (1974)
A study of fibrinolytic activity in sickle-cell patients during asymptomatic periods has shown a normal fibrinolytic response to exercise and local heat to the arm. During vasoocclusive crises there was no significant decrease in fibrinolytic activity. These results contrast with earlier reports of decreased fibrinolysis during crisis and a suggestion that fibrinolytic activators might be of value in preventing vasoocclusive episodes. Patients in painful crisis showed a significant rise in fibrinogen concentration and fall in platelet count. The former may contribute to localized vascular sludging by increasing whole-blood viscosity, while the latter probably results from local trapping of platelets in areas of sickling or from subsequent splenic sequestration of damaged platelets. There was no evidence of disseminated, as opposed to localized, intravascular coagulation during crisis.